Redefining Feminine Strength and Vulnerability: A Gender Performative Analysis of Wonder Woman 1984 (2020) Movie - Lie, Jesslyn Quaneisha; Satriyo, Nathanael Raditya Putra; Ricky, Gabriel Andrea; Sihaloho, Caesar Allie (Jurnal Pendidikan Makarios, 2024)
This study investigates the critical issue in Wonder Woman (1984) in feminist perspective, by using Judith Butler’s (1990) theory of gender performativity. The movie explores the interconnectedness of feminine strength and vulnerability, traditional gender roles, and the theme of power and agency. Diana Prince’s journey reflects the societal pressure on women to embody both strength and emotional complexity, while Barbara Minerva’s transformation into Cheetah represents the internalization of masculine ideals of power. As the results: 1) The movie demonstrates that feminine strength and vulnerability can coexist, subverting the notion that power must align solely with masculine ideals. 2) Wonder Woman (1984) critiques traditional gender roles by showing how women’s autonomy is often constrained by societal expectations, particularly in relationships and social responsibilities. 3) The movie reveals a significant difference in how power and agency are explored between male and female characters, with male characters like Max Lord wielding unchecked power, while female characters must navigate moral and societal limitations. Through Butler’s framework, Wonder Woman 1984 critiques traditional gender norms, suggesting that true empowerment comes from redefining power and success beyond patriarchal structures. This article is expected to enhance feminist discourse in movie analysis by offering a more profound insight into how media portrayals of women both challenge and uphold societal standards. Hence, it enhances critical conversations around gender, power, and identity, encouraging further exploration of how movies can influence and reflect progressing perspectives on gender equality.